How Poles indicate people and objects, and what they think of certain forms of pointing gestures - Jarmołowicz-Nowikow, Ewa (Lingua Posnaniensis, 2014)
The first gesture produced by children before they utter their first word has the form of an extended index finger. T his gesture is often described as a prototypical pointing gesture and is regarded as a universal display of intentional communication in most explored cultures (Volterra et al. 2011; Tomasello 2007). It is interesting, however, that in many cultures, a pointing gesture realized with index finger extended is regarded as rude, especially when made by adults or by children past the age of learning to speak. T he aim of this paper is to answer some questions concerning the form and usage of pointing gestures performed by native speakers of Polish. T his paper is focused on potential determinants of the form of pointing gestures, on the Polish cultural norms for indicating people and objects, as well as on the perception of pointing gestures. T he study is based on two experiments and a survey.